The effect of network convergence on digital culture industry: Model construction of network industrial economics and empirical study on China - Panqiang Niu; Anang Masduki; Xigen Li; Filosa Gita Sukmono (Informasi, 2021)
This paper constructs the model of network economics to study the effect of different levels of network convergence on the digital culture industry. Then uses regression models and mediating effect models to test the effect mechanism of network convergence on the digital culture industry of China.  This paper used panel data to conduct an empirical study. The data in this paper were quarterly. The time range was from the first quarter of 2009 to the third quarter of 2013 for 19 quarters.The three data types in econometrics are time series data, cross-sectional data, and panel data.The main conclusions are as follows. Network convergence brings positive policy effects and adverse capital effects. The impact of network convergence on firm performance of the digital culture industry is not statistically significant, and this effect also has no indirect effects on the test of mediating effect. However, network convergence indirectly leads to the reduction of operating costs of the digital culture industry. The indirect effect is brought by the chain mediating effect of policy effect and capital effect. The study could provide a reference for other countries and regions. Meanwhile, it can be used to analyze the impact of different media convergence on digital industries.